From boats to buildings: the impact of urbanization on Malay settlement in Pulau Duyong, Terengganu - Abdullah, Azli (Universiti Teknologi MARA, Perak, 2025)
This study examines the socio-economic and cultural impacts of urbanization on Pulau Duyong, Terengganu, traditionally known for its boat-making industry. The research aims to understand how infrastructure growth, land reclamation, and improved access have transformed the island’s physical and socio-economic landscape. Using historical analysis, surveys and observations, the study finds that urbanization has expanded educational and healthcare facilities and economic prospects while reducing traditional trades and causing youth migration. The study also explores eco-tourism and cultural tourism as potential solutions for maintaining local industries and preserving Malay cultural identity. This study demands united efforts between sustainable development approaches to create an equilibrium between Malay economic expansion and community preservation. Recommendations focus on promoting eco-tourism, investing in sustainable infrastructure, supporting traditional trades, developing educational programs, and engaging the Malay community in planning processes in the future.